Innovation of Public Service E-Court of Bojonegoro Religious Court: Study Case of Divorce Case - Agustina, Laily Rahma; Taufiq, Ahmad; Swasanti, Ida (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This article aims to describe the innovation of the Bojonegoro Religious Court in resolving divorce cases to create good public services and to find out whether there are challenges in developing this e-court application innovation. The problem focuses on how effective e-court innovation is in improving the quality of public services, especially divorce handling and identifying obstacles and aspects that need to be improved so that it becomes a sustainable application in the future. In order to approach this problem, a theoretical reference from M. Roger is used, with 5 innovation attributes, namely: relative advantage, suitability, complexity, possibility of trying and ease of observation. Data was collected through a case study approach, interviews, observations, and analyzed qualitatively. This study concludes that in this modern era the government is required to create a service that can make things easier for society through the use of technology. One of the uses of technology made by the Supreme Court is e-court. E-Court is an electronic administration service that allows people to conduct matters online. This service aims to make it easier for people who are constrained by time and costs, as well as reaching areas farthest from the court. Several service features available in e-court include online case registration (E-Filling), electronic down payment estimates (E-Payment), online summons (E-Summons) and online trials (E-Litigation).